Ensuring Ecological Sustainability of Agro-Cenoses Through the Use of Organic Fertilizers and Biological Preparations (Wire Insights: Journal of Innovation Insights, 2024)
The combined use of organic fertilizers and Rizokom-1 biopreparation in ensuring the ecological stability of the cotton agrocenosis showed an increase in the number of beneficial microorganisms living in the soil. Experiments were carried out in 2019-2021 in the conditions of irrigated typical gray soils of Kashkadarya region.